2019
DOI: 10.1097/jsm.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Injury Pattern in Icelandic Elite Male Handball Players

Abstract: The results indicate a higher rate of overuse injuries in low back/pelvic region and shoulders than in comparable studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 16 publications
9
63
0
3
Order By: Relevance
“…Handball has consistently been one of the top three to eight sports in the Olympic Summer Games in terms of the proportion of athletes who receive injuries, where 18-27% of the players are injured during the games (67,(82)(83)(84). The injury rates reported from studies in adult players during the competitive handball season range from 15-31.7/1,000 match hours and 0.24-3.4/1,000 training hours (70,73,79,85,86). The injury rates during tournaments are higher and range from 82.1-145/1,000/1,000 match hours (67,68,81,87).…”
Section: Injury Incidencementioning
confidence: 99%
“…Handball has consistently been one of the top three to eight sports in the Olympic Summer Games in terms of the proportion of athletes who receive injuries, where 18-27% of the players are injured during the games (67,(82)(83)(84). The injury rates reported from studies in adult players during the competitive handball season range from 15-31.7/1,000 match hours and 0.24-3.4/1,000 training hours (70,73,79,85,86). The injury rates during tournaments are higher and range from 82.1-145/1,000/1,000 match hours (67,68,81,87).…”
Section: Injury Incidencementioning
confidence: 99%
“…Even though some of the junior players matched the senior players in height and weight, they had lower scores irrespective to their anthropometrics. These results raise questions about possible correlations between age related differences in trunk strength and stability and the high prevalence of time loss injuries in the low back region in Icelandic male handball (45) . Firm conclusions are not possible, but the data represent a platform for further research.…”
Section: Level Of Playmentioning
confidence: 90%
“…Considering their high score in tests 3, 8 and 9 (Table 1), which all test for mobility and flexibility, it seems reasonable to suggest that lack of trunk strength and stability plays a role in their low score in test 1. Research on Icelandic elite handball players has shown that one-third of overuse injuries resulting in absence from participation were located in the low back/pelvic region (45) . This demonstrates a need for further knowledge regarding training methods and possible risk factors.…”
Section: Level Of Playmentioning
confidence: 99%
“…Time-loss-Verletzungen von 11-14 pro 1000 Stunden Spiel und 0,6-2,4 pro 1000 Stunden Training beschrieben [2][3][4]. Demgegenüber zeigten neuere Studien im professionellen Bereich eine höhere Verletzungsrate mit 15-24 pro 1000 Stunden Spiel und 1,1-3,7 pro 1000 Stunden Training [5][6][7]. Neueste Daten der Verwaltungsberufsgenossenschaft (VBG), die alle versicherungspflichtigen Verletzungen aus der 1. und 2.…”
Section: Verletzungsmusterunclassified